The Racial Oppression in America’s Mass Incarceration - Sorrentino, Marcella (2018)
This paper seeks to expose the racial oppression embedded within the United States' practice of mass incarceration and will provide recommendations to ameliorate this discriminatory practice that harshly and inequitably impacts people of color. Many minority communities are stuck in a continuous cycle of poverty and incarceration, in part because they are targeted and oppressed by the criminal justice system more frequently than middle class white communities. Consequently, incarcerated people of color exhibit high rates of recidivism because of being stripped of resources and being sent back to impoverished, drug-ridden neighborhoods. The War on Drugs in the 1980s and the continuance of poor relations between law enforcement and minority communities are significant contributing factors that have led to the mass incarceration of racial minority groups. The economic, political, and societal oppression of minority communities that unquestionably contributes to mass incarceration will be highlighted throughout this paper. Creating policies that involve transforming the U.S. legal system and providing communal support will be crucial in eradicating this systemic racial oppression